Legal Certainty of Acquittal Decision (Vrijspraak) Against Perpetrators Of 3 Kg Lpg Gas Adulteration (Case Study of Decision No. 350/Pid.Sus/2022/PN.Mdn) - Dwi Dris Juliansyah; Citra Ramadhan; Riswan Munthe (CERED Indonesia Institute, 2025)
LPG (Liquified Petroleum Gas) subsidies are provided by the government to low-income communities with the aim of making it easily accessible to the public. The act of mixing subsidized LPG is harmful to public interest and causes public concern. This is evident in Medan city, where cases of mixing subsidized 3 Kg LPG cylinders into non-subsidized 12 Kg cylinders occur. The research problem is how the legal certainty of acquittal rulings for perpetrators of 3 Kg LPG mixing is ensured and how judges consider the acquittal of such perpetrators based on the ruling No. 350/Pid.Sus/2022/PN.Mdn. This type of research is empirical normative juridical research. The data sources use secondary data. Data collection techniques are carried out through literature review and field studies, and data analysis is conducted qualitatively. Based on the results of the discussion, it was found that the legal certainty of acquittal against the perpetrators of LPG 3 Kg adulteration is determined by examining the indicators of criminal punishment for the offenders involved, referring to the evidence found and presented in court, so that the panel of judges is convinced that the perpetrators can be declared legally proven and have indeed committed the criminal act of subsidized LPG adulteration. The judge's consideration regarding the acquittal of the perpetrator of mixing 3 Kg LPG gas based on Decision No. 350/Pid.Sus/2022/PN.Mdn was made by the panel of judges based on the considerations in the first, second, and third alternative charges of the Public Prosecutor, which according to the facts of the trial were not proven in their entirety. Therefore, based on these facts, the defendant must be acquitted of the charges brought by the Public Prosecutor and from all legal claims. Based on the legal facts in the trial, the panel of judges found no evidence that the activity was carried out on the orders of the defendant.